Movse's Dasxuranc'i history of the Aghuans - Movsēs, Daskhurantsʻi, 10. yy. ([Dandenong South, Victoria] Los Angeles)
3 cilt (1. c. xviii, 198 sayfa ; 2. c. xvi, 342 sayfa ; 3. c. xx, 149 sayfa)
Keywords: “A major source for the history of the indigenous Aghuan people of Caucasia from the earliest times to about A.D. 988. Aghuania (also Arran, Aghbania, Caucasian Albania) comprised parts of modern Dagestan and Azerbaijan, Armenia's eastern neighbor. Its ancient peoples and their numerous languages were noted occasionally by classical Greek and Latin authors. Like the neighboring Armenians, the Aghuans were part of the Iranian-Zoroastrian culture-world for at least a millennium. Their royalty and nobility had marriage ties with their counterparts in Iran and Armenia. Also, like Armenia, Aghuania was among the countries early visited by the Apostles; and the Aghuan and Armenian churches were frequently united“ --